Marketing Strategy of Arabica Coffee Products on Harapan Maju Group in Kintamani, Bali, Indonesia - I Gusti Ayu Widari; Kadek Surya Adi Saputra; Gusti Ngurah Aditya Krisnawan (Warmadewa University Press, 2023)
This study aims to identify internal and external factors and alternative marketing strategies for Arabica coffee in the Harapan Maju Group, Kintamani, Bangli, Bali, Indonesia. The method in this study is the SWOT analysis technique. The results showed that the internal environmental factors that had the highest score on the strength indicator were having a consistent taste of coffee products, having many variants of coffee products, and human resources influencing the quality and quantity of coffee products produced. The indicators of weakness are erratic yields which affect the ups and downs of sales, promotions that are not maximized, and the lack of knowledge of human resources for digital marketing through social media. Meanwhile, the external environmental factors in the opportunity indicator are the growth in domestic coffee consumption which continues to increase, the development of coffee management technology, and the government's efforts to assist group coffee marketing. The threat indicators are that similar competitors are superior in following market trends quickly, the bargaining position of consumers is getting higher, and there is a lot of imported coffee coming from outside. Eight alternative strategies that the Harapan Maju Group needs to carry out to increase profits include: expanding the marketing network, improving the quality of service to consumers, strengthening cooperation or collaboration with government agencies, improving the quality of human resource management with training, increasing promotional activities with digital media setting competitive prices for the development of globalization, increasing the use of technology in Arabica coffee business management, and streamlining Arabica coffee operational costs